2020
DOI: 10.1177/0003489420943910
|View full text |Cite|
|
Sign up to set email alerts
|

A Prospective Randomized Trial of N-butyl-cyanoacrylate + Metacryloxysulfolane Adhesive versus Suture Alone for Grafting in Rhinoplasty: 9 year Follow-up

Abstract: Objective: Use of cyanoacrylate glue in facial plastic surgery is still controversial due to the absence of long-term follow up showing the results. Aim of our study is comparing the long-term outcomes of N-butyl-cyanoacrylate + Metacryloxysulfolane versus traditional sutures in rhinoplasty. Methods: Prospective comparative study. One hundred forty-two patients affected by ptotic nasal tip were included and randomized in two groups. In group A, the surgeon fixed the graft by using the glue and suture and in gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Cyanoacrylate adhesives are approved only for superficial use or vascular embolization (because of the potential for chronic inflammation from degradation products), although the authors have reported favorable results in rhinoplasty with follow-up to 9 years. 11 Two 5-0 Prolene sutures establish fixation points for the graft situated between the medial crura; the first suture is placed on the medial aspect of the graft, and the second suture is secured just under the portion of the cartilage that will form the new dome, thereby determining tip characteristics. Edges are beveled to avoid angularity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyanoacrylate adhesives are approved only for superficial use or vascular embolization (because of the potential for chronic inflammation from degradation products), although the authors have reported favorable results in rhinoplasty with follow-up to 9 years. 11 Two 5-0 Prolene sutures establish fixation points for the graft situated between the medial crura; the first suture is placed on the medial aspect of the graft, and the second suture is secured just under the portion of the cartilage that will form the new dome, thereby determining tip characteristics. Edges are beveled to avoid angularity.…”
Section: Methodsmentioning
confidence: 99%
“…The conchal graft is then incised along the long axis and folded outward, with concave surface facing outward, and fixed at its fulcrum with a single suture or a drop of glue (Glubran) 11 (Fig. 1).…”
Section: Surgical Techniquementioning
confidence: 99%